Analysing the passive cooling performance of natural ventilation system design mimicked from solar-powered African termite mounds for varied building configurations - Jumawan, Hazel U.; Juanga, Jean Marie V. (2020)
Urban development is accompanied by large-scale construction ofmidrise and high-rise projects. Along with this is the need to power thesebuildings, most often through mechanical means. Consequently, the buildingand construction industry are accountable for 36% of the global energyconsumption and 40% of CO2 emissions.This study aims to address this issue through exploring the applicationof a biomimetic approach to building ventilation. The concept of biomimicryhas come from the concept that nature has confronted similar problemsfaced by the human society, and it has created sustainable solutions thathave been filtered through millions of years of evolution. The main objectiveof the study is to analyze the efficiency of a natural ventilation system designinspired from the solar-powered African termite mounds (ATM) for variedbuilding configurations using a computer simulation software (IES VE 2019).The simulation results of the study show that air movement in theATM-inspired natural ventilation system design did not coincide with theexpected results following the solar heat-driven ventilation mechanism intermite mounds. The results of the CFD simulation for interior wind velocityshow that there are slower wind velocities in the ATM-inspired simulationmodels compared to the conventional model, from 0 to 0.55 mLs and greaterthan 1.2 mLs in some areas. The operative temperature in the interiorhallways of the ATM-inspired design models are significantly lower thanthose in the conventional model.From the data gathered, it can be concluded that the diurnal thermalcycles of air flow in African termite mound do not occur similarly in midriseand high-rise buildings incorporated with ventilation system inspired fromAfrican termite mounds. Although interior wind velocity is greater in theconventional models for all building footprints, the ATM-inspired naturalventilation system design resulted to lower temperatures in the interiorhallways of the building with no exterior openings.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020